Carbon budget of common urban tree species in an arid city based on life cycle assessment - Ruijing Zhang; Li Wang; Xiaoge Tian; Yuyang Song (PLoS ONE, 2026)
Urban trees sequester and store carbon through photosynthesis, while their planting and maintenance processes consume energy and materials, resulting in the release of carbon back into the atmosphere. Therefore, a comprehensive and scientifically rigorous assessment of the net carbon sequestration capacity of landscape trees must account for both carbon uptake and emissions. In this study, three types of urban green spaces—parks, roadsides, and residential areas—were selected as research sites. Based on the life cycle assessment, biomass equation method and emission factor method, the life cycle carbon sequestration and carbon emissions of the main tree species in Shihezi City were calculated. The genotype main effect plus genotype-by-environment interaction (GGE) biplot and Pearson correlation analyses were employed to elucidate species–environment interactions across the three green space types and to identify management strategies for maximizing net carbon sequestration. The main findings were as follows: (1) The mean carbon storage per tree in parks (366.78 kgC tree -1 ) was significantly higher than that in roadsides (305.59 kgC tree -1 ) and residential green spaces (236.39 kgC tree -1 ), with Ulmus pumila exhibiting the highest per-tree carbon storage (595.39 kgC tree -1 ). (2) The order of carbon emissions in the whole life cycle is: park (461.15 kgC tree -1 )> roadside (395.48 kgC tree -1 )> residential area (283.65 kgC tree -1 ). Irrigation is the main emission source, accounting for more than 50% of the total carbon emissions in the whole life cycle. (3) Under current management practices, Ulmus pumila consistently maintained a positive life cycle carbon budget across all green space types, whereas some other large tree species showed positive carbon budgets only in specific green space types and had negative carbon budget in others. All small tree species exerted negative effects on the carbon sequestration function of urban green spaces across all three types of green space. Based on the findings of this study, strategies for low-carbon urban green space construction were proposed through enhancing carbon sequestration and reducing maintenance-related emissions.